1999
DOI: 10.1046/j.1365-3016.1999.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the registration of stillbirths < 500 g in Canada, 1985–95

Abstract: We assessed recent temporal trends in the registration of stillbirths in Canada, with particular regard to stillbirths < 500 g. Data from the Statistics Canada live birth and stillbirth databases for the period 1985-95 were used for the study. The primary analysis was restricted to data from 10 of the 12 provinces and territories of Canada. Data from Newfoundland were excluded because birthweight distributions were not available prior to 1990, and data from Ontario were excluded because of concerns about data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…Birth registration practices have also changed over the study period, as reflected by the dramatic rise in the registration of extremely premature live births [Howell and Blondel, 1994; Sachs et al, 1995; Sepkowitz, 1995; Joseph and Kramer, 1996] and stillbirths [Joseph et al, 1999]. Although the definition of a live birth did not change, the definition of a stillbirth (which included gestational age and/or birth weight criteria) changed slightly in some of the provinces and territories of Canada between 1985 and 1996 [Joseph et al, 1999]. Such minor changes cannot explain the gestational age‐dependent pattern of temporal change observed among congenital anomaly‐related fetal and infant deaths, however.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Birth registration practices have also changed over the study period, as reflected by the dramatic rise in the registration of extremely premature live births [Howell and Blondel, 1994; Sachs et al, 1995; Sepkowitz, 1995; Joseph and Kramer, 1996] and stillbirths [Joseph et al, 1999]. Although the definition of a live birth did not change, the definition of a stillbirth (which included gestational age and/or birth weight criteria) changed slightly in some of the provinces and territories of Canada between 1985 and 1996 [Joseph et al, 1999]. Such minor changes cannot explain the gestational age‐dependent pattern of temporal change observed among congenital anomaly‐related fetal and infant deaths, however.…”
Section: Discussionmentioning
confidence: 99%
“…During the study period, most Canadian provinces and territories defined a stillbirth as a fetal death with a gestational age ≥ 20 weeks or a birth weight ≥ 500 g birth weight, while a few provinces/territories used a single birth weight (fetal death with a birth weight ≥ 500 g) or a single gestational age criterion (fetal death at a gestational age ≥ 20 weeks) [Joseph et al, 1999]. Some provinces changed their stillbirth definition from one of three definitions listed above to another during the study period (e.g., in 1994 Saskatchewan changed its definition of stillbirth from fetal death at a gestational age ≥ 20 weeks or a birth weight ≥ 500 g to fetal death at a birth weight ≥ 500 g).…”
Section: Methodsmentioning
confidence: 99%
“…As our data source did not identify triplet sets, we recreated sets using identifiers such as birth date, maternal age and province of residence (498 sets created for 1459 triplet births). During the study period, birth registration requirements in Canada meant that only fetal deaths ≥ 20 weeks gestation and/or ≥500 g birthweight were registered as stillbirths 26 …”
Section: Methodsmentioning
confidence: 99%
“…International comparisons show a mixed picture: reports from Norway and North America show a similar increase in low birthweight (Daltveit et al, 1999;Joseph et al, 1999;Branum & Schoendorf, 2002), but there has been no such increase reported for Sweden (Odlind et al, 2003) or Scotland (Fairley, 2005).…”
Section: Trends In Low Birthweightmentioning
confidence: 99%